Comparing Symmetric-Asymmetric Decentralization for Reducing Regional Tension: Indonesia and Thailand Experience - M. R. Khairul Muluk; Anurat Anantanatorn (Indonesian Association for Public Administration, 2023)
In recent years, the growing number of public administration literature has concerned the effectiveness of decentralization to deal with ethnic conflicts. This issue is rising up due to the several failure reports of decentralization to manage the social conflicts and regional tension that possibly evolve into secessionism. This paper intended to explore the performance of symmetric and asymmetric decentralization to manage social conflicts that occurred in Indonesia and Thailand. This descriptive study was conducted through a qualitative approach and strengthened by analytical thinking exposure. Papua province, Indonesia, and some provinces in southern Thailand had been selected as the case study due to their political decision for implementing asymmetric and symmetric decentralization to manage ethnic conflict in each region. The result shows that either symmetric or asymmetric decentralization might be thought of as one of the viable solutions to managing social conflicts. However, both of these decentralization configurations may generate pros and cons impact. It is suggested that policy makers recognize the consequence of each implementation to consider appropriate decision- making. The analysis of this paper shows that symmetric decentralization tends to promote effectiveness and efficiency while asymmetric decentralization will be closer to tolerance and equality.